Economic Empowerment of Fishermen's Wives - Financial Management and Digital Marketing Assistance Program for Sustainable MSME Development in Makassar Tallo District: Pemberdayaan Ekonomi Istri Nelayan - Program Pendampingan Manajemen Keuangan Dan Pemasaran Digital Untuk Pengembangan UMKM Berkelanjutan Di Kecamatan Tallo Makassar - Ulfa Sufyaningsi; Samsuddin; Agus Darmawan; Andi Fahri Faisal; Wiwin Anggriani; Nurul Khumairah; Mardiana; Tri Widayati Putri; Muhammad Ikbal; Iin Octaviana Hutagaol; Dafiuddin Salim; Sukmatica Slamet; Ilham; Fadly Yashari Soumena (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Fishermen's wives play a vital role in supporting the coastal family economy through various productive economic activities, such as seafood processing and business diversification. However, they face challenges such as limited access to financial services, inadequate management knowledge, and insufficient utilization of digital technology. A community service program conducted in Tallo Subdistrict, Makassar, focused on enhancing financial literacy, market research, and digital marketing skills for micro and small enterprises (MSEs) managed by fishermen's wives. The program included training, mentoring, and monitoring over three months to improve financial management, digital platform adoption, and marketing strategies. The results showed significant increases in sales revenue, distribution networks, and the use of social media among participants. This success underscores the importance of a holistic approach to economic empowerment, which not only improves MSE performance but also contributes to the economic stability of fishermen's families and sustainable coastal economic development.